Who comes when the world goes Code Blue? A novel method of exploring job advertisements for COVID‐19 in health care. Issue 3 (30th November 2020) - Watts, Rory D.; Bowles, Devin C.; Fisher, Colleen; Li, Ian W.
Abstract: Aim: To explore the health workforce responses to COVID‐19. Design: Analysis of job advertisements. Methods: We collected advertisements for healthcare jobs which were caused by and in response to COVID‐19 between 4 March–17 April 2020 for the United States, Canada, United Kingdom, Australia and New Zealand. We collected information on the date of the advertisement, position advertised and location. We categorized job positions into three categories: frontline, coordination and decision support. Results: We found 952 job advertisements, 72% of which were from the United States. There was a lag period between reported COVID‐19‐confirmed cases and job advertisements by several weeks. Nurses were the most advertised position in every country. Frontline workers were substantially more demanded than coordination or decision‐support roles. Job advertisements are a novel data source which leverages a readily available information about how workforces respond to a pandemic. The initial phases of the response emphasise the importance of frontline workers, especially nurses.